Tele-branding in TVIII: the network as brand and the programme as brand - Johnson, Catherine (Routledge, 2007)
In the era of TVIII, characterized by deregulation, multimedia conglomeration, expansion and increased competition, branding has emerged as a central industrial practice. Focusing on the case of HBO, a particularly successful brand in TVIII, this article argues that branding can be understood not simply as a feature of television networks, but also as a characteristic of television programmes. It begins by examining how the network as brand is constructed and conveyed to the consumer through the use of logos, slogans and programmes. The role of programmes in the construction of brand identity is then complicated by examining the sale of programmes abroad, where programmes can be seen to contribute to the brand identity of more than one network. The article then goes on to examine programme merchandising, an increasingly central strategy in TVIII. Through an analysis of different merchandising strategies the article argues that programmes have come to act as brands in their own right, and demonstrates that the academic study of branding not only reveals the development of new industrial practices, but also offers a way of understanding the television programme and its consumption by viewers in a period when the texts of television are increasingly extended across a range of media platforms.